EFFECT OF BETEL NUTS AND TOBACCO DERIVATIVES ON ANTIOXIDANTS AND MICRONUTRIENTS IN ORAL SUBMUCOUS FIBROSIS AND ORAL CANCER PATIENTS IN GUJARAT POPULATION - MONIKA PATEL,; GAURANG ANANDPARA,; SANDHYA PILLAI, (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: In our previous study, we have find the significance of biochemical markers between precancerous and cancerous subject with normal healthy individuals in Gujarat population, taking into consideration the severity of biochemical markers in cancerous condition. We felt that other than comparison, effect of betel nuts and tobacco derivatives on antioxidants and micronutrients has required further evaluation to develop a better understanding. The objective of the present study is to measure the interdependence of antioxidants and micronutrients in oral submucous fibrosis and oral cancer patients and find its significance. Method: In this study, a total of 150 patients in which 50 diagnosed PMD patients and 50 diagnosed oral cancer patients with 50 healthy non-tobacco consuming were selected as a control group. Five to seven milliliters of venous blood was collected under aseptic precautions with patients consent. All the parameters were analyzed by standard methods using fully auto-analyzed with a ready-to-use kit. Result: This research was conducted on 150 patients, out of which 50 diagnosed potential malignant disorder patients and 50 oral squamous cell carcinoma patients matched with 50 healthy control individuals. Average age of patients with PMD and OSCC was 55.6±9.74-and that of control group was 35.83±8.90 years. Student t-test showed that there was a significant difference between the two groups with regard to age. Of the 100 patients with PMD, 72 (72% of total) were men and 28 (28% of total) were women. Among the individuals in the control group (n=50), 35 persons (70% of total) were men and 15 (30% of total) were women. Chi-square test showed that there was no significant difference between the two groups in terms of sex (p=0.891). The copper levels of PMD and OSCC, respectively, were 153.57±7.68 and 164.43±15.75. The value was statistically compared with OSCC which had significantly higher levels than healthy control (102.53±22.1). The iron levels of PMD and OSCC, respectively, were 77.62±15.27 and 50.04±19.97. The value was statistically compared with OSCC which had significantly lower levels than (138.4±13.2) healthy control. The Vitamin C levels of PMD and OSCC, respectively, are 0.55±0.10 and 0.44±0.9. The value was statistically compared to the OSCC which had significantly lower than 1.09±0.17 control. The Vitamin E levels of PMD and OSCC, respectively, 1.18±0.16 and 0.8±0.12 values were statistically compared the OSCC which had significantly lower levels than (1.39±3.64) healthy control. Conclusion: In our finding, Vitamin C showed positive correlation with serum iron and serum copper with malignant disorders. Trace elements and antioxidants exhibited interdependence in both physiologic and pathologic states such as oral cancer.